Islamisation and ethnic identity of the chinese minority in Malaysia - Meng, N.Y. ([s.n], 2011)
This study of Chinese minority set out to provide a profile of the Chinese community in Kelantan situated at the northern-east coast of Peninsular Malaysia. Kelantan is significantly peculiar in the study of Chinese minority‟s response towards Islamisation policies for two reasons. First, the state has been under the strong grip of an Islamic opposition party, i.e. Islamic Party of Malaysia (PAS) for four consecutive electoral terms (1990, 1995, 1999 and 2004). Second, Muslims constitute 95% of the total population in Kelantan whilst the Chinese constitutes merely 4% of the state population (Census of Population, 2000). The 4% Chinese ethnic minority in Kelantan are constantly reminded of their ethnicity after many generations of co-existence and even mixed marriages with the local people. Despite their excellent proficiency in the Kelantanese dialect, their adaptation to the local culture and religious practices of the Muslims are not without tension. Controversies often arise whenever the state government intends to impose Islamic values on the Muslims as well as the non-Muslims. The Chinese still consciously draw and maintain ethnic boundaries with the local Malay Muslims, particularly with regard to conversion to Islam. However, such resistance was significant among the devoted Buddhists and Christians, but not the Chinese who think highly of Islamic way of life. Given the primacy of Malay political hegemony and the constitutional status of Islam, the Chinese minority in Kelantan experienced both gradual and drastic changes incorporated in the state and national policies, particularly policies concerning religio-politics, socio-economy, education, language and culture. Alerted or alarmed by their deteriorating socio-political rights as well as the peripheral status of their cultural identity as ethnic Chinese, the Chinese community consciously set up boundary that is used to differentiate the Chinese non-Muslims with the Malay-Muslims („others‟) by means of safeguarding their religion, language and cultural identity in a Muslim dominated society. Confining to survey and personal interview conducted with the Chinese respondents,preliminary findings showed that there were five significant factors, i.e. politics, religion, integration, understanding of Islam and ethnocentrism that determine the responses towards Islamisation policies, as well as the notion of Islamic State. The Chinese in Kelantan appreciate religious freedom thus far and they hope the state government would continue to respect cultural differences in both public and private domains. This study is particularly useful to help us understand the perceptions and feelings of the Chinese minority in Malaysia. It is hoped that such views are taken into consideration when strategising future state and national administrative policies.